Paraganglioma of the Renal Pelvis: A Case Report and Review of Literature. (November 2017) - Yi, Cheng; Han, Lin; Yang, Rui; Yu, Junfeng
Purpose: Paraganglioma, a kind of pheochromocytoma originating from embryonic neural crest, is a rare neuroendocrine neoplasm commonly located at extra-adrenal areas such as head, neck, and abdomen. There are a few reports on renal paragangliomas; fewer than 5 reported cases are renal pelvic paragangliomas, including our case. Methods: Our patient, who had not experienced headache, hypertension, or palpitation, was founded to have a fixed mass in the left renal pelvis incidentally. Ultrasonography and computed tomography (CT) demonstrated a heterogeneous mass before surgery, and histopathologic test subsequently revealed that the infrequent mass was paraganglioma. Results: During 6 months follow-up, ultrasonography and CT examinations showed no signs of recurrence or metastasis. Conclusions: The present case report confirms surgery as the standard to treat patients with paraganglioma. We present this case to serve as a reminder of suspected paraganglioma when it has occurred in renal pelvis.